Africa's COVID-19 Situation in Focus and Recent Happenings: A Mini Review - Hagan, John Elvis; Ahinkorah, Bright Opoku; Seidu, Abdul-Aziz; Ameyaw, Edward Kwabena; Schack, Thomas (Frontiers in Public Health, 2020)
Given that COVID-19 has creeped into Africa, a major public health crisis or threat continues to linger on the continent. Many local governments and various stakeholders groups have stepped up their efforts for early detection and management of COVID-19 across their population. This mini review highlights the current trend in Africa, history and general epidemiological information on the virus. Current ongoing efforts (e.g., improving testing capacity) and some effective ways (e.g., intensified surveillance, quick detection, contact tracing, isolation measures [e.g., quarantine], and social distancing) of preventing and managing COVID-19 in Africa are described. The review concludes by emphasizing the need for public health infrastructure development and capacity building for the current pandemic and potential future outbreaks. Additionally, regular public health educational campaigns are urgently required. Future epidemiological studies to ascertain case fatality and mortality trends across the continent for policy directions are necessary.